Does alcohol contribute to accident and emergency department attendance in elderly people?. Issue 4 (July 1996) - van der Pol, V; Rodgers, H; Aitken, P; James, O; Curless, R
Abstract : OBJECTIVE: To evaluate the possible contribution of alcohol to presentation of elderly subjects at a hospital accident and emergency (A&E) department. METHODS: 105 patients aged 70 years and over who attended the department were interviewed by a single observer using a structured questionnaire based on previously validated general population surveys. Details of alcohol consumption within the previous 24 hours were recorded. Usual consumption of alcohol in the preceding 12 months was estimated by the quantity frequency method. Alcohol dependence was screened for by the CAGE questionnaire. An assessment of disability was made using the Barthel index. Breath alcohol was measured. RESULTS: In only 2% of attenders was alcohol thought to be a contributory factor. Breath alcohol measurements were technically unsatisfactory in this age group. Regular drinkers were functionally and socially more independent than non-regular drinkers. Drinking patterns in this age group may partly be determined by the physical ability to obtain alcohol. CONCLUSIONS: Alcohol was not found to be a major factor in A&E attendance in elderly people.